UK Vessel Health and Preservation (VHP) Framework: a commentary on the updated VHP 2020. Issue 4 (July 2021) - Hallam, Carole; Denton, Andrea; Weston, Valya; Dunn, Helen; Jackson, Tim; Keeling, Susan; Hill, Steve
Background: In 2016, a UK vessel health and preservation (VHP) framework was developed to support healthcare staff to select the most appropriate vascular access device for patients requiring intravenous therapy. The VHP framework was based on available evidence and expert consensus. The VHP was based on available evidence and expert consensus. Development of the VHP 2020 Framework: A multidisciplinary team reviewed the original UK VHP framework and considered new published evidence, national and international guidelines and expert opinion. A literature search was performed using Cinahl and Medline, incorporating a variety of terms linked to vascular access devices, assessment and selection. Articles published in and after 2014 in English were included. Twelve articles were found to be relevant including three evidence-based guidelines, two randomised control trials and one systematic review. Findings: Three main studies provided the evidence for the update: the MAGIC study that assessed the appropriateness of peripherally inserted central catheters in patients; a study that utilised the 'A-DIVA scale' to predict the likelihood of difficult venous access; and a study that incorporated an 'I-DECIDED tool' for peripheral intravenous catheter assessment and decision-making for device removal. In addition, published guidelines provided evidence that the original advice on appropriate osmolarity of medicines for peripheral administration needed updating. Conclusion: The 2020 UK VHP framework reflects latest evidence-based research and guidelines, providing healthcare staff updated guidance to assist in maintaining good practice in vascular access assessment and device selection and patient safety.